Effects of human chorionic gonadotropin on the normal testicular tissue of rats - Altoé,Patricia Magnago (2014)
PURPOSE: To investigate the effects of human chorionic gonadotropin (hCG) on the testicular tissue of young male rats.METHODS: Male Wistar rats were assigned to groups (10 rats/group).Control Group received subcutaneous saline solution; Group 1 received hCG 50UI/Kg/dose; and Group 2 received hCG 100UI/Kg/dose, daily for 15 days. Half was submitted to bilateral orchiectomy on the 16th day and the other half 45 days after the beginning of the hormone application. Testicles were weighed, measured and has their volumes determined. The diameter of the tubules and the thickness of the seminiferous epithelium were measured.RESULTS: Control Group presented the highest values of testicles volume and weight. Rats in the Control presented normal histology. In G1 and G2 atrophy of the seminiferous tubules, apoptosis of germ cells and multinucleated giant cells were observed. Comparing groups, in the first operation Control rats had higher diameter values. In the second operation, the Control was only different from G1. As for thickness, Control had higher values in both operations. Comparing the time of operation, the diameter values were higher in G1 and G2 in the second operation. For all groups, the thickness of the epithelium was higher in the second operation.CONCLUSIONS: Human chorionic gonadotropin is gonadotoxic in rats. This effect was temporary and can affect reproductive potential. The total recovery of testicular damage in the studied range could not be proved, and the effects were not dose-dependent.